Consumer preferences toward organic food and the moderating role of knowledge: a case of Pakistan and Malaysia - Umair Kashif; Chen Hong; Snovia Naseem; Waris Ali Khan; Muhammad Waqar Akram (2020)
The present study aimed to identify the elements of the Theory of Planned Behaviour along with health consciousness and determine the role of knowledge as a moderating variable in Pakistan and Malaysia. Three hundred and forty-one observations from Pakistan and 280 observations from Malaysia were acquired through questionnaire; while, confirmatory factor analysis and structural equation modelling was applied for the analysis. The magnitude of the results varied across both countries; however, attitude, subjective norms and health consciousness, as well as their interaction terms, were significant predictors, whereas, perceived behavioural control and its knowledge interaction terms had insignificant impacts on the purchase intentions of consumers for both countries. This research will help to further understand about consumer perception in the purchase of organic food items, which will assist retailers, advertisers and manufacturers in developing strategies for such products.